LUG’AT MUKAMMALLIGI-TA’LIM-TARBIYA GAROVI (Yangi lug’atlar misolida) - Ruzimov, Sh. (SCIENCE and SOCIETY, 2020)
In the article compiling principles of Sanjar Nazarov, Feruza Nazarova, Nigora Adizova, Dilbar Poltayeva’s English-Uzbek dictionaries, were investigated and shown their advantages and disadvantages with examples and practical recommendations for improving compiling principles of the next generation dictionaries were worked out with the help of comparative-typological method, componential analysis and classification method.Worked out recommendations can be used in the further perfection and improvement of the quality of the translation dictionaries.